Growth and longevity in giant barrel sponges: Redwoods of the reef or Pines in the Indo-Pacific?. Issue 1 (December 2018) - McGrath, Emily; Woods, Lisa; Jompa, Jamaluddin; Haris, Abdul; Bell, James
Abstract Describing life history dynamics of functionally important species is critical for successful management. Barrel sponges (Xestospongia spp.) fill ecologically important roles on coral reefs due to their large size and water column interactions. Studies of CaribbeanX. muta suggest they may be up to 1000 s of years old. However, nothing is known of barrel sponge growth rates outside the Caribbean. We assessed Indo-Pacific barrel sponge demography with a focus on specific growth rate (SGR), density, and mean volume across four sites of varying habitat quality. Four growth models were compared using Akaike's Information Criterion using a multi-model inference approach. Age was extrapolated and validated based on sponge size on a shipwreck of known age. Sponges from different sites showed differences in density, volume gained, and mean volume, but not growth rates. Interestingly, SGRs were slightly slower than that ofX. muta, yet growth models supported rapid growth; Indo-Pacific sponges were over twice as old as published estimates of comparably sizedX. muta (53–55 as compared to 23 years of age, respectively), although extrapolation errors are likely to increase with sponge size. This suggests that barrel sponge growth rates in the Indo-Pacific might be more comparable to Pines rather than Redwoods.